Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Language variables in administrative health data hosted at ICES - Batista, Ricardo; Prud'homme, Denis; Tanuseputro, Peter; Manuel, Doug (L'institut du Savoir Monfort and ICES Ottawa, 2019)
Research on linguistic minorities have revealed important disparities in Canada. Numerous analyses have identified the need for further studies looking at health status, healthcare utilization access barriers and quality of care affecting francophone living in a minority contexts (FLMCs) in Canada.1 The value and need to improve access and use of valid health information to support the planification of health and social services is well documented; however, important gaps and challenges have been recognized, which limit further progress in understanding the disparities in health and health care for some subpopulations.

Les données linguistiques pour la recherche et la planification en santé : possibilité et limites pour l'étude des francophones en situation minoritaire - Bouchard, Louise; Lizotte, Mathieu (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Malgré de remarquables avancées de recherche sur la problématique de la santé en contexte francophone minoritaire, la disponibilité de variables linguistiques complètes et cohérentes dans les bases de données nationales de santé demeure lacunaire et fragmentée, constituant un défi considérable pour l’étude de la santé des membres des communautés francophones en situation minoritaire (CFSM) et la planification de services adaptés à cette population dispersée. Cet article offre un bilan exhaustif des possibilités et des limites des données disponibles permettant l’étude de la santé des CFSM. Ce faisant, il met en lumière une série de problèmes méthodologiques, dont le manque de données pertinentes, l’absence de variables standardisées et les faibles effectifs pour l’analyse régionale, entre autres. Ces lacunes entravent considérablement la capacité des chercheuses et chercheurs à étudier les conditions et les besoins spécifiques des CFSM en ce qui concerne la santé et la planification de la santé. Mots-clés : données linguistiques, problèmes méthodologiques, francophone, minorité, quantification

Organiser les connaissances sur la santé des CLOSM - Bouchard, Louise; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2022)
Dans un contexte de production intensive de connaissances, les auteurs propose un cadre d’analyse pour aider les chercheurs à repérer les études qui les intéressent dans le domaine de la santé des CLOSM

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

Améliorer les services et les soins offerts aux communautés francophones en situation minoritaire au Canada : entre recherche, dialogue et formation. - Collin, Stéphanie; Bouchard, Pier; Vézina, Sylvain; Cormier, Manon (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Au regard de l’amélioration des services et soins de santé offerts aux communautés francophones en situation minoritaire (CFSM), la programmation du Groupe de recherche et d’innovation sur l’organisation des services de santé (GRIOSS) de l’Université de Moncton a constamment évolué. Depuis 2009, les travaux de l’équipe de recherche ont été névralgiques, développant une compréhension plus fine de divers enjeux « évolutifs du terrain » s’inscrivant dans des thèmes généraux comme la gestion et l’organisation des services et soins de santé ainsi que la gouvernance. Cet article présente, sous forme d’un récit historique, l’évolution de la programmation de recherche du GRIOSS et une synthèse des résultats de recherche ainsi que des extrants ayant influencé la pratique. Un élément central du bilan : les savoirs issus de ces recherches ont servi, au fil du temps, à nourrir la réflexion commune et le dialogue s’est traduit par des changements sociaux durables au sein des CFSM. Mots-clés : communautés francophones en situation minoritaire, accès aux services de santé dans la langue officielle de son choix, offre active, recherche-action, dialogue

La mobilisation des connaissances en santé dans les CFSM [infographie] - Consortium national de formation en santé (2021)

Un projet de formation qui a fait et qui continue à faire ses preuves. La phase II du Consortium national de formation en santé 2003-2008 : cinq années déterminantes. - Consortium national de formation en santé

La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services - Consortium national de formation en santé; Société Santé en français (Consortium national de formation en santé et Société Santé en français, 2010)

Equity, safety & health outcomes: The case for a national minimum data standard around health workforce language data in Canada - Demers, Chantale; Richard, Lise; Bourgeault, Ivy. Lynn

Qui sont les francophones ? Analyse des définitions selon les variables du recensement de 2001 - Forgues, Éric; Landry, Rodrigue; Boudreau, Jonathan (Institut canadien de recherche sur les minorités linguistiques et Consortium national de formation en santé, 2009)

Les données administratives et d’enquêtes sur l’état de santé et l’accès aux services des communautés francophones en situation minoritaire : potentiel d’analyse et état de situation. Rapport - Gaboury, Isabelle; Guignard Noël, Josée; Forgues, Éric; Bouchard, Louise (Consortium national de formation en santé, 2009)

Populations de langue officielle en situation minoritaire selon différentes méthodes de dénombrement. Rapport - Guignard Noël, Josée; Forgues, Éric (Institut canadien de recherche sur les minorités linguistiques, 2020)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Comment inclure la variable linguistique dans la demande de subvention [infographie] - Institut du Savoir Montfort; Unité de soutien de la SRAP en Ontario

La mobilisation des connaissances en santé dans les petites communautés francophones en situation minoritaire. Ses défis, ses conditions de succès - Johnson, Marc. L.; Cimon, Virginie; Dancause, Luc; Forest, Mariève (SOCIUS recherche et conseils, 2021)

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistique Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°001) - Lafrenière, Sylvie (Statistics Canada, 2009)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Health Data for Linguistic Minority Group Research in Canada: Proof-of-Concept Centralized Health Care Metadata Repository Development and Usability Study - Martin-Schreiber, Vincent; Peixoto, Cayden; Batista, Ricardo; Belanger, Christopher; Tanuseputro, Peter; Hsu, Amy T; Bjerre, Lise M (JMIR Infodemiology, 2026)
Background Language barriers between Canadian patients and health care providers are associated with poorer health outcomes, including decreased patient safety and quality of care, misdiagnosis and longer treatment initiation times, and increased mortality. However, research exploring language as a social determinant of health is limited, as Canadian health data are scattered across many jurisdictions, each with its own policies and procedures. This fragmentation makes it difficult for researchers to identify, locate, and use existing data. This paper presents the results of a pilot study that attempts to address this gap by creating a metadata repository (MDR) to act as a central source of information about what data are available at which data holdings across Canada. Objective This project aimed to (1) create a proof-of-concept MDR for Canadian health data at the variable level; (2) identify and label language-related variables existing within the MDR data; and (3) develop an interactive, public-facing web application to let users browse and search the MDR. Methods Metadata were collected from 5 Canadian health data sources, including 4 provincial data holdings and 1 national survey, and pooled to create a data repository. Then, we performed bottom-up labeling of language-related variables within the pooled metadata by first using a search string algorithm across all variable labels, names, and definitions and then consensus screening these variables using a derived, standardized definition of language or linguistic variables. Using the Shiny web framework in R, we then developed an openly accessible web application to allow users to search the proof-of-concept MDR. Results A total of 850,343 variables were collected and included in the repository, with most coming from Ontario (n=712,037, 83.7%) and Manitoba (n=97,051, 11.4%) provincial data holdings. Among all variables in the repository, 213,696 (25.1%) were confirmed to be language related. Conclusions Developing a national MDR would be a transformative opportunity for Canadian researchers to leverage the full scope of Canadian health administrative data. Although a top-down approach with consistent engagement of and collaboration between provincial data holdings and federal data agencies is ideal to develop a national MDR, this study demonstrates the feasibility of a bottom-up approach in contributing to this overarching goal.

Comparison of sampling methods for hard-to-reach Francophone populations: Yield and adequacy of advertisement and respondent-driven sampling - Ngwakongnwi, Emmanuel; King-Shier, athryn. M.; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude (Open medicine, 2014)
Francophones who live outside the primarily French-speaking province of Quebec, Canada, risk being excluded from research by lack of a sampling frame. We examined the adequacy of random sampling, advertising, and respondent-driven sampling for recruitment of francophones for survey research. Methods: We recruited francophones residing in the city of Calgary, Alberta, through advertising and respondentdriven sampling. These 2 samples were then compared with a random subsample of Calgary francophones derived from the 2006 Canadian Community Health Survey (CCHS). We assessed the effectiveness of advertising and respondent-driven sampling in relation to the CCHS sample by comparing demographic characteristics and selected items from the CCHS (specifically self-reported general health status, perceived weight, and having a family doctor). Results: We recruited 120 francophones through advertising and 145 through respondent-driven sampling; the random sample from the CCHS consisted of 259 records. The samples derived from advertising and respondentdriven sampling differed from the CCHS in terms of age (mean ages 41.0, 37.6, and 42.5 years, respectively), sex (proportion of males 26.1%, 40.6%, and 56.6%, respectively), education (college or higher 86.7% , 77.9% , and 59.1%, respectively), place of birth (immigrants accounting for 45.8%, 55.2%, and 3.7%, respectively), and not having a regular medical doctor (16.7%, 34.5%, and 16.6%, respectively). Differences were not tested statistically because of limitations on the analysis of CCHS data imposed by Statistics Canada. Interpretation: The samples generated exclusively through advertising and respondent-driven sampling were not representative of the gold standard sample from the CCHS. Use of such biased samples for research studies could generate misleading results.

The new Inclusive definition of Francophone (IDF) - Office of Francophone Affairs (2020)

Obligations linguistiques et recherche en santé : analyse du rapport des IRSC aux communautés francophones en situation minoritaire - Pelbois, Christelle; Bouchard, Louise (Minorités linguistiques et société, 2026)
Le Canada compte deux langues officielles, mais la recherche en santé menée sur et par les communautés francophones en situation minoritaire demeure fragilisée par l’anglicisation. Cet article analyse les dynamiques sociales qui structurent cette recherche et les tensions entre exigences d’excellence scientifique et reconnaissance de sa légitimité. Le cas des Instituts de recherche en santé du Canada, visés par une enquête du Commissariat aux langues officielles, illustre les limites actuelles du soutien institutionnel. La récente modernisation de la Loi sur les langues officielles qui reconnaît l’inégalité de statut des langues et les besoins différenciés, ouvre toutefois des perspectives d’équilibrage. Canada has two official languages, yet health research conducted by and on Francophone minority communities remains vulnerable to the effects of anglicization. This article examines the social dynamics shaping this research and the tensions between scientific excellence requirements and recognition of its legitimacy. The case of the Canadian Institutes of Health Research (CIHR), subject to an investigation by the Office of the Commissioner of Official Languages, highlights current institutional shortcomings. The recent modernization of the Official Languages Act, which acknowledges the unequal status of languages and differentiated needs, nonetheless opens new opportunities to rebalance these dynamics.

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Joint Position Statement on the Linguistic Variable - Regroupement des Entités de planification des services de santé en français de l'Ontario (2013)

État de la situation Collecte des données liées à la santé des francophones du Nouveau-Brunswick - Réseau-action formation et recherche (RAFR)

La variable linguistique : une donnée essentielle pour mieux planifier les services de santé et de mieux-être au Nouveau-Brunswick - Réseau-action Formation et recherche; Société Santé et Mieux-être en français (2018)

La variable linguistique en recherche. L'importance de la langue dans le processus de recherche [infographie] - Réseau de recherche appliquée sur la santé des francophones de l'Ontario (2012)

Better data for better planning: The challenge of evidence-based data for sound planning of French-Language health services in Ontario - Réseau des services de santé en français de l’Est de l’Ontario (The challenge of evidence-based data for sound planning of French-Language health services in Ontario, 2013)

Des données pour mieux planifier: Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario - Réseau des services de santé en français de l’Est de l’Ontario (Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario, 2013)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Recommandation du Réseau. Collecte des données linguistiques - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales

Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2020)

Framework for the Analysis of Health and Social Services Access and Integration for Official Language Minority Communities - Savard, Jacinthe; Savard, Sébastien; Drolet, Marie; De Moissac, Danielle; Kubina, Lucy-Ann; van Kemenade, Solange; Benoit, Josée; Couturier, Yves (2020)

Access to health and social services for Quebec’s English-Speaking Minority Communities: Recent challenges, legislative context, and research recommendations. - Shoumarova, Lina (Quebec English-Speaking Communities Research Network, 2024)

Accès aux soins de santé pour les communautés québécoises d’expression anglaise – Principaux enjeux et besoins en matière de recherche - Shoumarova, Lina; Pocock, Joanne; Donovan, Patrick; O'Donnell, Lorraine (Université Concordia, 2025)
Le présent document résume les travaux de recherche qui ont été menés récemment sur l’accès aux services de santé et aux services sociaux pour la communauté de langue officielle en situation minoritaire (CLOSM) anglophone du Québec. S’appuyant sur la Bibliographie sur le Québec anglophone, la Bibliothèque ouverte du savoir communautaire et le centre de documentation du Réseau communautaire de santé et de services sociaux (CHSSN), il met en lumière les principaux thèmes traités, les lacunes dans la recherche et les domaines où d’autres travaux de recherche doivent être menés en priorité.

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)